Performance of ZnO-Kaolin for Palm Oil Mill Secondary Effluent (POMSE) Treatment via Photocatalytic Reactor - Sahilan, Nuramira Aliah; Awang, Zarizi; Hairom, Nur Hanis Hayati (Progress in Engineering Application and Technology, 2023)
This study focus on how to treat palm oil mill secondary effluent (POMSE) better than the commercial method. Wastewater discharge from palm oil premise is not following the regulations defined by EQA 1974. It is proven that traditional treatment technique does not give an effective result in treating POMSE. The traditionalonal method took a ltimeriod to treat the effluent water rather ting this photocatalytic process. The objective that has to achieve in this study is to synthesize ZnO - kaolin for the low grade under different ratios to obtain the optimum performance, to explore the implementation of ZnO- Kaolin for POMSE treatment via MPR and only focus on photocatalytic process and lastly to analyze the different type of kaolin for the cost factor. The method used in this study is precipitation method for synthesizing zinc oxide and photocatalytic reactor for treating POMSE. Lastly, the optimum ratio gained from this study is 1:5 with the most effective performance up to 30.9% of percentage BOD removal among others.